Unraveling the Role of Immune Checkpoints in Leishmaniasis - de Freitas e Silva, Rafael; von Stebut, Esther (Frontiers in Immunology, 2021)
Leishmaniasis are Neglected Tropical Diseases affecting millions of people every year in at least 98 countries and is one of the major unsolved world health issues. Leishmania is a parasitic protozoa which are transmitted by infected sandflies and in the host they mainly infect macrophages. Immunity elicited against those parasites is complex and immune checkpoints play a key role regulating its function. T cell receptors and their respective ligands, such as PD-1, CTLA-4, CD200, CD40, OX40, HVEM, LIGHT, 2B4 and TIM-3 have been characterized for their role in regulating adaptive immunity against different pathogens. However, the exact role those receptors perform during Leishmania infections remains to be better determined. This article addresses the key role immune checkpoints play during Leishmania infections, the limiting factors and translational implications.